Influence of rice (Oryza satiya)-cultivation method and cropping system on nutrient status of soil and productivity in Vertisols - SUBBAIAH, S V; KUMER, R MAHENDER (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1990-91 and 1991-92 to find out the influence of cultivation method of rice (Oryza sativa L.) and lice-based cropping systems on nutrient status of soil and total productivity of the system in Vertisols. The methods of rice cultivation such as direct sowing dry seed in dry seed-bed, direct sowing of sprouted seed on puddled wet soil and transplanting did not influence significantly the available nutrient status of the soil. Growing pigeonpea or redgram [Cajanus cajan (L.) Millsp.] in winter season (rabi) increased the soil-organic matter and the N and P status of the soil. It led to higher rice -equivalent yield in rice-redgram sequence (6 314 kg/ha) during succeeding year in comparison with that of rice-sorghum [Sorghum bicolor (L.) Moench]. But rice-safflower (Carthamus tinctorius L.) sequence recorded the overall best result in terms of rice-equivalent yield. Final nutrient status of the soil indicated that rice-pigeonpea sequence gives higher content of soil-organic carbon and the available Nand P, whereas K and Zn availability declines in rice-sorghum and rice-safflower sequences.